Initial public offering : voluntary disclosure and underpricing in Singapore IPOs. - Hoi, Kah Mun. (2010)
Until the recent global financial crisis, there has been an increase in the number of companies seeking Initial Public Offerings (IPOs) in the global financial markets, including Singapore. Companies seek IPOs for a myriad of reasons. Some companies have financial objectives (e.g. raising capital) while some have strategic reasons (e.g. raising the company’s profile in the market). A common issue that companies may face in their IPOs is first day underpricing. In our research, we aim to establish a relationship between the voluntary disclosure of information in companies’ IPO prospectus and their first day underpricing within the Singapore market. Our interest lies in three measures of voluntary disclosure: 1) the dollar details on the use-of-proceeds, 2) the provision of financial forward-looking statement (i.e. dividend and/or earnings forecast) and 3) the reason/s that firms provide to the public for conducting an IPO. In general, our research shows that the dollar detail on the use-of-proceeds and the provision of financial forward-looking statements do not aid in reducing first day underpricing. More significantly, companies seeking IPOs for strategic purposes suffer more first day underpricing.